Architectural barriers in the passage of the deficient physicist to the hospitals of Sobral, Ceará - Paulo César de Almeida; Antonia Eliana de Araújo Aragão; Lorita Marlena Freitag Pagliuca; Kátia Nêyla de Freitas Macêdo (Universidade Federal de Goias, 2006)
Quantitative study on architectural barriers in the passage of the deficient physicist to the hospitals of Sobral, Ceará, with the objective of mapear the access conditions architectural of the carriers of physical deficiency to the four hospitals of the mentioned city. Supported in NBR 9050 of the ABNT, it used instrument type check-list, whose collection of data occurred in May of 2004. The analysis statistics evidenced absence of bands for pedestrians and only one to show degradation of curb in strategical points; unproctected public works and particular of fences; sidewalk with holes and making uneven; half of free avenues of holes; visible plates of transit signaling in tree of hospital; passage for the signaled institution; but it does not have traffic lights in strategical points. One hospital possess degradation of guides; absence of parking for carrying person of physical deficiency. As it was concluded, has architectural barriers in the way of house / hospital. With this the hospitals require better structures with sights to minimize the barriers architectural in the passage of the deficient physicist to these services.